Expression of PD-L1 and prognosis in breast cancer: a meta-analysis - Zhang, Minghui (Oncotarget, 2017)
The associations between programmed cell death ligand 1 (PD-L1) and the prognosis of various cancers have always been a research topic of considerable interest. However, the prognostic value of PD-L1 in breast cancer patients remains a controversial subject. We aimed to assess the association between PD-L1 protein expression and clinicopathological features and the impact of this relationship on breast cancer survival. We performed a systematic search of the PubMed, EMBASE, and Cochrane Library databases to determine the correlations among PD-L1 expression, clinicopathological features and overall survival (OS). A total of 5 studies containing 2,546 cases were included in the analysis. The combined hazard ratio (HR) and its 95% confidence interval (CI) for OS were 1.76 (95% CI 1.09–2.82; P=0.02) for patients with tumors exhibiting PD-L1 overexpression. The pooled odds ratios (ORs) indicated that PD-L1 expression was associated with positive lymph node metastasis, higher histological grades, estrogen receptor (ER)-negativity, and triple-negative breast cancer (TNBC). Our findings indicate that PD-L1 expression is a promising biomarker for the prognosis of breast cancer, and may be helpful to clinicians aiming to select the appropriate immunotherapy for breast cancer.